FTIR characteristics of coal seam structure in Xishan Mining Area - Wenxu LIANG; Zhipeng HAN; Wei FU (Meikuang Anquan)
In order to study the characteristics of coal structure in Xishan Mining area, the chemical structure of raw coal samples from 7 different coal seams in Tunlan Mine in Xishan Mining area was analyzed and characterized by Fourier infrared spectroscopy (FTIR). The results of spectral characteristic curves show that: the wide frequency band below 3 600 cm−1 of each coal seam sample is caused by OH stretching vibration; the maximum absorption of the sample is in the vicinity of 3 430-3 400 cm−1; coal samples 02#, 2#, 7#, 8#, and 9# vibrate strongly in the 800-1 800 cm−1 frequency band, in which there are mostly oxygen-containing functional groups, mainly including hydroxyl group (alcohol hydroxyl group and phenolic hydroxyl group), carboxyl group, carbonyl group, etc. These groups themselves have strong hydrophilicity, increasing the water content of coal internal structure, resulting in a decrease in their own energy density. It is not conducive to the deep processing and utilization of coal. Through the study of FTIR absorption peak attribution, spectrum analysis and fitting, the aryl carbon ratio (fa-FTIR) value based on FTIR technology related to coal maturity was obtained; the regression model between the experimental value of fa-FTIR and the theoretical arylene carbon rate (fa-T) is established, and the positive correlation coefficient R2=0.804 is obtained, indicating that the arylene carbon rate calculated by FTIR is reliable. By studying the correlation between the metamorphic degree of coal (the maximum reflectance Rmax) and infrared structural parameters, it is found that with the increase of Rmax, the aryl carbon rate fa-FTIR increases, and the hydrocarbon generation potential ‘A’ decreases. At this stage, coalification will increase the aromatic hydrocarbons in coal.